If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + 3 = 10x + -45 Reorder the terms: 3 + 18x = 10x + -45 Reorder the terms: 3 + 18x = -45 + 10x Solving 3 + 18x = -45 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 3 + 18x + -10x = -45 + 10x + -10x Combine like terms: 18x + -10x = 8x 3 + 8x = -45 + 10x + -10x Combine like terms: 10x + -10x = 0 3 + 8x = -45 + 0 3 + 8x = -45 Add '-3' to each side of the equation. 3 + -3 + 8x = -45 + -3 Combine like terms: 3 + -3 = 0 0 + 8x = -45 + -3 8x = -45 + -3 Combine like terms: -45 + -3 = -48 8x = -48 Divide each side by '8'. x = -6 Simplifying x = -6
| -(m-6)=3m+4 | | x^2+4x-18=40 | | 6x+8-2=-24 | | 12/m-3 | | -5x+16+-8(x+1)=6x | | 2x^2-3y^2=12 | | 4m/m-3 | | -3+7=-5 | | -6x-x+10=15-7x | | 1-n-5+16=-n-2n | | (9v+36)(v^2-6v+5)=0 | | -(x+7)-6=-20+6x | | N^2+16=-8n | | 3[4x-5(y-2)]= | | -3x-1=x-17 | | -5=9+4 | | X+4(x+2)=12 | | -2(9+4s)=34 | | 5a^2= | | 3a+12=6a+7 | | 4x^3-6x-6=0 | | -7(1-5h)=21 | | 3x+2y+2x+5z+7y+2z= | | 5x+13y=11 | | 3x(4)=180 | | 4.5(6.2)=n | | 3(3y-3)-2(y-6)= | | m^2-3m+5=0 | | 35-6x=-(1-3x) | | 60+x+68+68=180 | | 48b+24= | | 4.5(6.2)= |